(untitled) (The Lumbini Journal of Business and Economics, 2022)
Customer satisfaction is the degree of satisfaction provided by the goods or services of a company as measured by the number of repeat customers. It is also the marketing term that measures how products or services supplied by a company meet a customer’s expectations. This study has developed a theoretical framework to analyze the customer satisfaction of supermarkets in Rupandehi district with the major defining variables service delivery, other facilities, product variety and product price. The findings of a sample set of respondents (380) analyzed using multiple regression analysis indicate that customers are satisfied with service delivery, product variety and other facilities, while they are not satisfied with product price. The study concluded that most preferred factor for customer to visit supermarket is product variety and availability. Most important factor that peoples consider for the satisfaction of supermarket are product variety, product price and service delivery. Other facility provided by the supermarket has not significant effect on the customer satisfaction.